Penggunaan buku komik “bahasa Indonesia bagi penutur asing (BIPA) 1” dan pengaruhnya terhadap hasil belajar peserta BIPA - Ramliyana, Randi (Jurnal Bahasa Indonesia bagi Penutur Asing, 2019)
Indonesian Language Learning for Foreign Speakers (BIPA) is interesting because Indonesian language becomes the second language learning for BIPA participants. Many obstacles are happened during learning BIPA, one of communication problem between teacher and participant. Communication problem in delivering material BIPA class can overcome with visual language. Visual language will be made in the form of comics as and teach BIPA. Comics as a medium of learning has long been applied to give a positive impact during the learning process Comic media in addition to fun, also always linked can increase interest in reading, and develop vocabulary in the language used comic As a first step to arouse interest in reading especially those who do not like reading In addition to comics also improve all other language skills, such as talking and listening. Comics is able to package all learners with a fun language skills. So, comics have a close related with language learning, because it is always associated with improving language skills therefore, research aims to design the book in the form of comic on learning BIPA language. Researchers hope this research will be useful for the world of language education, especially BIPA, in Indonesia and provide new solutions by using comics as a fun learning media and able to increase interest and motivation to learn BIPA participants